Travel Conscious Effects and Wonderful Brands Indonesia Against Visitors' Interest in Maimun Palace Medan - Apri Wati Br Barus (Enrichment : Journal of Management, 2021)
This study aims to examine and analyze the influence of tourist awareness and Wonderful Brand Indonesia simultaneously and partially on the interest of visitors in the Palace of Maimun Medan. The type of data used in this study is the type of quantitative data while the data source used in the study is primary data. Data collection methods used are data collection techniques through the Object questionnaire in this study are all visitors to the Palace of Maimun Medan. The population in this study was all visitors who came to Istana Maimun Medan. Research samples were 80 people. The analytical tool used is SPSS. The data analysis method used in this research is Multiple Regression Analysis method. The results of the research show that the tourism conscious and Brand Wonderful Indonesia variables have a positive effect on visitor interest in the Istana Maimun Medan. The results also showed that simultaneous and partial tourism conscious variables and the Indonesian Wonderful Brand had a significant positive effect on visitor interest in the Istana Maimun Medan..